Profil Residu Insektisida Organofosfat di Kawasan Produksi Bawang Merah (Allium Ascalonicum L.) Kabupaten Brebes Jawa Tengah - Nining, Euis; Nazli, Rizal Sjarief Sjaiful; Mas’ud, Zainal Alim; Machfud, Machfud; Sobir, Sobir (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2019)
Excessive use of pesticides can have an impact on the environment, including the loss of pesticide residues in soil and agricultural products. The purpose of this study was to determine the spreading of organophosphate pesticide residues in the shallot production area of Brebes Regency, Central Java. Research locations were two districts selected by purposive sampling based on production area, namely Kersana and Wanasari Districts. Organophosphate compounds analyzed include chlorpyrifos, paration, profenofos, diazinon, fenitrotion, metidation and malation. Organophosphate residue analysis was carried out on seven soil samples and seven shallot products. Pesticide residue analysis was carried out using the standard method by using a gas chromatography device with an electron capture detector. Based on analysis, seven residues of organophosphate pesticides were chlorpyrifos, paration, profenofos, diazinon, fenitrotion, metidation and malation, spread in Kersana District, and six pesticides residues (except profenofos) spread in Wanasari District. In soil samples, the highest residues obtained in two districts were chlorpyrifos compounds, chlorpyrifos compounds in Kersana District was higher than Wanasari District. In the shallot sample, the highest residues in two districts are diazinon compounds, diazinon compounds in the sample of Kersana District was higher than Wanasari District. There were several samples of shallot product contained organophosphate residue exceed the maximum concentration of residual limit (RML).